A PC composition resistant to moisture and heat and easy to process, and its preparation method and application

By adding titanium dioxide and active additives to the polycarbonate, the problems of low impact retention rate and large color difference under high humidity and heat conditions are solved, and the high humidity and heat aging performance and good processing performance are improved.

CN114752200BActive Publication Date: 2025-03-25KINGFA SCI & TECH CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202210242867.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-03-11
Publication Date
2025-03-25
Estimated Expiration
2042-03-11

AI Technical Summary

Technical Problem

The existing polycarbonate has low impact retention rate and large chromatic aberration under high humidity and heat conditions, and the chromatic aberration increases significantly after multiple processing, affecting its performance and application.

Method used

By adding a specific amount of titanium dioxide and active additives to the polycarbonate, the titanium dioxide has a catalytic cross-linking effect, changing the molecular segment structure and protecting the ester bonds; the active additive reacts with the PC-terminal carboxyl group to form a stable urea compound and slowing down the hydrolysis autocatalytic effect.

Benefits of technology

The moisture-heat aging and processing performance of polycarbonate is improved. The impact retention rate after high-temperature cooking is higher than 50%, and the color change rate is lower than 5% after passing the machine for 5 times, which significantly improves moisture-heat stability and color difference.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003543350390000021
    Figure BDA0003543350390000021
  • Figure BDA0003543350390000061
    Figure BDA0003543350390000061
  • Figure BDA0003543350390000081
    Figure BDA0003543350390000081
Patent Text Reader

Abstract

The present invention discloses a moisture-heat-resistant and well-processed PC composition, a preparation method and an application thereof, wherein the PC composition comprises the following components by weight: 60 to 99 parts of polycarbonate, 0.5 to 3 parts of titanium dioxide, and 0.1 to 1 part of an active auxiliary agent, wherein the active auxiliary agent is an imide polymer or an epoxy polymer. The PC composition of the present invention has excellent moisture-heat-resistant and well-processed performance, an impact retention rate after high-temperature steaming of more than 50%, and good recycling and processing performance, and a color change rate of less than 5 after 5 times of machine processing, and can be used in the preparation of household appliances and electronic appliances.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of engineering plastics, and more specifically to a moisture-heat-resistant and well-processed PC composition, a preparation method and application thereof. Background Art

[0002] Polycarbonate (PC) is an engineering plastic with excellent performance. It has good comprehensive performance, high mechanical strength, good impact resistance, dimensional stability, good heat resistance, and good electrical insulation. It is widely used in home appliances, digital products, IT products and other fields.

[0003] Since there are carbonate bonds in the polycarbonate molecular chain that are sensitive to water and heat, and the polar C=O group is easy to form hydrogen bonds with water, it is hydrophilic and therefore more susceptible to the influence of moisture in the aging environment. In high temperature, oxygen and humid environments, the molecular chain of PC will degrade to varying degrees, seriously affecting its performance. Due to its acid and alkali resistance and water resistance, its wet heat aging performance is poor, and it is difficult to maintain its performance during the processing of multiple cycles, which limits its use in outdoor electronic appliances.

[0004] It is a common method to improve the wet heat aging performance of polycarbonate by adding a hydrolysis stabilizer. WO85 / 02622A1 discloses that phosphorous acid, phenylphosphonic acid and phosphorous acid derivatives substituted with fluorinated hydrocarbon groups are used to improve the color stability of polycarbonate-polyester alloys. JP 02-018332B discloses the use of 2-20 ppm phosphorous acid and 50-300 ppm tris(2,6-di-tert-butylphenyl)phosphite to stabilize and prepare a polycarbonate resin with good mechanical properties, hot water resistance and reduced yellowing under thermal stress. WO 2010 / 063381 A1 discloses a hydrolysis-stable and processing-stable polycarbonate composition, which improves hydrolysis stability by adding a P-OH phosphorus compound. WO 2009 / 118114 A1 discloses that hydroxyl-functionalized mono- and polycarboxylic acids, as well as phosphoric acid and sodium / potassium salts of phosphoric acid improve the hydrolysis stability of polycarbonate compositions. CN109021534A discloses a high temperature and high humidity resistant polycarbonate composition and a preparation method thereof, wherein the high temperature and high humidity resistance is achieved through the synergistic effect of a toughening agent and a chain extender. CN112552668A discloses a long-term stable polycarbonate composition and a preparation method thereof, wherein a block copolymer with epoxy or anhydride functional groups improves the wet heat stability.

[0005] The addition of acid, chain extender and toughening agent described in the above prior art can make polycarbonate have a higher impact retention rate, but there are still serious surface defects under wet and hot storage conditions, such as surface material flowers or whitening defects, and large color differences under multiple processing conditions. Summary of the invention

[0006] The primary purpose of the present invention is to overcome the problems of low impact retention rate, large color difference and large color difference after multiple processing of existing polycarbonate under high humidity and heat conditions, and to provide a PC composition resistant to humidity and heat and good processing. The PC composition provided by the present invention has excellent humidity and heat aging resistance and good processing performance, the impact retention rate after high temperature cooking is higher than 50%, and the color change rate after 5 times of machine is lower than 5.

[0007] Another object of the present invention is to provide a method for preparing the above-mentioned moisture-heat-resistant and well-processable PC composition.

[0008] Another object of the present invention is to provide the application of the above-mentioned moisture-heat-resistant and well-processable PC composition.

[0009] The above-mentioned object of the present invention is achieved by the following technical solutions:

[0010] A moisture-heat-resistant and well-processable PC composition comprises the following components in parts by weight:

[0011]

[0012] Wherein, the active auxiliary agent is an imine polymer and / or an epoxy polymer.

[0013] The present invention adds a specific amount of titanium dioxide and an active agent to polycarbonate. The titanium dioxide has a catalytic cross-linking effect, can change the molecular segment structure of the polycarbonate in the early stage of degradation, protect the ester bond and the aromatic ring-isopropylidene bond, and reduce the chain breakage; and the active agent can react with the terminal carboxyl group of PC and the carboxylic acid generated by the decomposition of PC to generate a stable urea-based compound without side effects, thereby slowing down the autocatalytic effect of polycarbonate hydrolysis, solving the problem of the decline in comprehensive performance of PC materials caused by hydrolysis. The two act synergistically to improve the impact performance of polycarbonate after wet heat aging and improve the color difference. In addition, due to the poor stability of the active agent itself, its processing stability is poor, and the color difference is significantly improved after multiple machine passes. After multiple tests, the inventor of the present invention found that adding a certain amount of titanium dioxide at the same time can reduce discoloration.

[0014] If the molecular weight of polycarbonate is too low, the end group content is high, the active points are many, and it is more likely to degrade during processing. If the molecular weight is too high, the thermal aging mechanism is more likely to cause Fils rearrangement, and it is easy to cross-link to produce color-forming substances, resulting in large color changes.

[0015] Preferably, the weight average molecular weight of the polycarbonate is 10,000-40,000.

[0016] More preferably, the weight average molecular weight of the polycarbonate is 20,000-30,000.

[0017] It should be noted that the weight average molecular weight of the polycarbonate of the present invention is determined by gel permeation chromatography (GPC) according to GB / T27843-2011 Chemical polymer low molecular weight component content determination.

[0018] Preferably, the average particle size of the titanium dioxide is 0.23-0.3 μm.

[0019] The polycarbonate of the present invention can also be recycled PC, such as optical disks and buckets.

[0020] Conventional imine polymers and epoxy polymers in the art can be used in the present invention. Generally, the imine polymer is one or more of sterically hindered aromatic carbodiimide, monocarbodiimide, and polycarbodiimide;

[0021] The epoxy polymer is one or more of styrene-acrylonitrile-glycidyl methacrylate, phenyl glycidyl ether, bisphenol A diglycidyl ether, tetra(phenyl glycidyl ether) ethane, and trimethoxy [3-(glycidyl ether) propyl] silane.

[0022] Preferably, the epoxy polymer is styrene-acrylonitrile-glycidyl methacrylate. Styrene-acrylonitrile-glycidyl methacrylate is a monomer having both acrylate double bonds and glycidyl ester groups, which can improve the stability of polycarbonate; in addition, the glycidyl ester group has high reactivity and is easy to react with active groups such as hydroxyl, carboxyl, and amino groups on polycarbonate.

[0023] The moisture and heat resistant and easy-to-process PC composition provided by the present invention may further include other conventional functional additives in the art to obtain more excellent or new performance. The types of various functional additives may be selected and adjusted according to actual needs.

[0024] Preferably, the other auxiliary agent is one or more of a stabilizer, a flame retardant, and a filler.

[0025] Specifically, the stabilizer is β-(4-hydroxyphenyl-3,5-di-tert-butyl) propionate, pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate], 1,3,5-(3,5-di-tert-butyl-4-hydroxyphenyl)-s-triazine-2,4,6(1H,3H,5H)trione, 1,3,5-trimethyl-2,4,6-(3,5-di-tert-butyl-4-hydroxybenzene, triethylene glycol bis[β-(3-tert-butyl-4-hydroxyphenyl) propionate] One or more of triethylene glycol bis-β-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate, tris(2,4-di-tert-butyl-4-hydroxyphenyl) phosphite (referred to as triester phosphite), benzyl propionate, bis(2,6-di-tert-butyl-4-methylphenyl) pentaerythritol diphosphate, bis(2,4-dicumylphenyl) pentaerythritol diphosphite or C20-24-α-maleic anhydride-2,2,6,6-tetramethylolefin.

[0026] The flame retardant is a phosphorus-based flame retardant and / or a sulfonate flame retardant, wherein the phosphorus-based flame retardant is selected from one or more of resorcinol tetraphenyl diphosphate (RDP), bis(diphenyl) phosphate of hydroquinone and bis(diphenyl) phosphate of bisphenol-A, chlorinated phosphazenes, phosphorus ester amides, phosphinic acid amides, tri(aziridinyl)phosphine oxide and polyorganophosphazenes; and the sulfonate flame retardant is potassium perfluorobutyl sulfonate.

[0027] The filler is selected from one or more of talc, mica, kaolin, barium sulfate and wollastonite.

[0028] The present invention also protects a method for preparing the moisture-heat-resistant and well-processed PC composition, comprising the following steps:

[0029] The polycarbonate, titanium dioxide, active additive and other additives are uniformly mixed, melt-extruded and granulated in a screw extruder to obtain a polycarbonate composition.

[0030] Preferably, the melting temperature is 260-280° C., and the rotation speed is 300 r / min.

[0031] The present invention also protects the use of the moisture-heat-resistant and well-processed PC composition in the preparation of outdoor PC products.

[0032] The outdoor PC products include but are not limited to routers, customer premise equipment (CPE) and outdoor electricity meters.

[0033] Compared with the prior art, the present invention has the following beneficial effects:

[0034] The invention prepares a PC composition by adding a specific amount of titanium dioxide and an active auxiliary agent into polycarbonate. The obtained PC composition has excellent wet heat aging resistance and good processing performance, good wet heat stability, a wet heat color difference of less than 5, an impact retention rate after high temperature cooking of more than 50%, and a color difference of less than 5 after passing through the machine for 5 times, and can be used in household appliances and electronic appliances. DETAILED DESCRIPTION

[0035] In order to more clearly and completely describe the technical solution of the present invention, the present invention is further described in detail through specific embodiments below. It should be understood that the specific embodiments described herein are only used to explain the present invention, and are not used to limit the present invention. Various changes can be made within the scope of the rights of the present invention.

[0036] The present invention will be further described below in conjunction with specific implementation modes.

[0037] Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the present technical field.

[0038] The raw materials in the embodiments and comparative examples can be obtained from commercial sources, as follows:

[0039] Polycarbonate 1: 1300-10NP, LG Chemical, weight average molecular weight 28,000;

[0040] Polycarbonate 2: Recycled CD PC, CQ-60A, Fuben Co., Ltd., weight average molecular weight 10,000;

[0041] Polycarbonate 3: 1300 03NP, LG Chemical, weight average molecular weight 40,000;

[0042] Polycarbonate 4: FB2560, SABIC, weight average molecular weight 50,000;

[0043] Polycarbonate 5: PC2100, SABIC, weight average molecular weight 20,000;

[0044] Polycarbonate 6: WY-106BR, Lihuayi Chemical, weight average molecular weight 30,000;

[0045] Active agent 1: epoxy polymer, styrene-acrylonitrile-glycidyl methacrylate, SAG-002, Yijiarong

[0046] Active agent 2: imine polymer, polycarbodiimide, Stabaxol P, Raschig, Germany

[0047] Active agent 3: epoxy polymer, bisphenol A diglycidyl ether, Shanghai Tongyuan Chemical Co., Ltd.;

[0048] Active agent 4: Imine polymer, bis(2,6-diisopropylphenyl)carbodiimide, AUSTAB SW-100, Shanghai Changhui Chemical Co., Ltd.

[0049] Active agent 5: Epoxy polymer, 3-glycidyloxypropyltriethoxysilane, A-187, Momentive, USA

[0050] Active agent 6: imine polymer, monocarbodiimide, AH3000 anti-hydrolysis agent, Dingfa Chemical Titanium Dioxide 1:: R103, average particle size 0.23μm, DuPont;

[0051] Titanium dioxide 2: R105, average particle size 0.3 μm, DuPont;

[0052] Titanium dioxide 3: R-960, average particle size 0.35 μm, DuPont;

[0053] Stabilizer: β-(4-hydroxyphenyl-3,5-di-tert-butyl) propionate, SONOX 1076, Linyi Sanfeng;

[0054] Flame retardant: potassium perfluorobutanesulfonate, FR2025, 3M;

[0055] Filler: talcum powder, SDC-9489, Xinda talcum powder;

[0056] The heat-resistant and easy-to-process PC compositions described in the examples and comparative examples are prepared by the following method:

[0057] The polycarbonate, titanium dioxide, active additive and other additives are uniformly mixed, melt-extruded and granulated in a screw extruder to obtain a polycarbonate composition, wherein the melting temperature is 260-280° C. and the rotation speed is 300 r / min.

[0058] Examples 1 to 10

[0059] Examples 1 to 10 provide a series of moisture-heat-resistant and easy-to-process PC compositions, and the amounts of the raw materials used are shown in Table 1.

[0060] Table 1 Amount of each raw material used in Examples 1 to 10 (parts by weight)

[0061] Example 1 2 3 4 5 6 7 8 9 10 Polycarbonate 1 80 60 99 / / / / / 80 80 Polycarbonate 2 / / / 80 / / / / / / Polycarbonate 3 / / / / 80 / / / / / Polycarbonate 4 / / / / / 80 / / / / Polycarbonate 5 / / / / / / 80 / / / Polycarbonate 6 / / / / / / / 80 / / Active agent 1 0.5 0.5 0.5 0.5 0.5 0.5 0.5 0.5 0.1 1 Titanium dioxide 1 1 1 1 1 1 1 1 1 1 1 Stabilizer / 1 1 / / / / / / / Flame retardants / / 2 / / / / / / / filler / 0.1 / / / / / / / /

[0062] Examples 11 to 20

[0063] Examples 11 to 20 provide a series of moisture-heat-resistant and easy-to-process PC compositions, and the amounts of the raw materials used are shown in Table 2.

[0064] Table 2 Amount of each raw material used in Examples 11 to 20 (parts by weight)

[0065]

[0066] Comparative Examples 1 to 7

[0067] Comparative Examples 1 to 7 provide a series of PC compositions, and the amount of each raw material used is shown in Table 3.

[0068] Table 3 Amount of each raw material used in Comparative Examples 1 to 7 (parts by weight)

[0069] Comparative Example 1 2 3 4 5 6 7 Polycarbonate 1 80 80 80 80 80 80 80 Active agent 1 / 0.5 / 2 0.05 0.5 0.5 Titanium dioxide 1 / / 0.5 1 1 0.2 4

[0070] Performance Testing

[0071] The performance tests were conducted on the moisture and heat resistant and well-processed PC compositions prepared in the examples and comparative examples.

[0072] (1) Hygrothermal stability test method:

[0073] The polycarbonate composition particles were added into an injection molding machine, melted at a temperature of 270°C to 290°C, and injection molded into 2mm*100*100 square plates. After being placed at 85°C and 85% humidity for 1000 hours, they were taken out, and after being placed at 23°C and 50% humidity for 48 hours, they were taken out and their appearance was observed.

[0074] Judgment criteria: Observe the bubble density and L value to determine the level.

[0075] level describe Level 1 No visible bubbles Level 2 No discoloration, a small amount of bubbles, bubbles occupying less than 50% of the total area Level 3 Obvious discoloration, bubbles occupy 50-80% of the total area Level 4 Obvious color change, many and dense bubbles, bubbles occupying more than 80% of the total area

[0076] (2) Method for determination of wet and hot color difference:

[0077] The polycarbonate composition particles were added into an injection molding machine, melted at a temperature of 270°C to 290°C, and injection molded into a 2mm*40*60 color plate. The color plates were placed at 85°C and 85% humidity for 1000 hours and then taken out. The color difference ΔE1 was tested after the color plates were placed at 23°C and 50% humidity for 48 hours.

[0078] ΔE1=(ΔL 2 +△a 2 +△b 2 ) 1 / 2

[0079] L represents lightness, a represents the difference between red and green, and b represents the difference between blue and yellow

[0080] ΔL, Δa, and Δb correspond to the differences of the indicators (L, a, b) before and after aging at 85°C and 85% humidity, respectively.

[0081] (3) Impact retention rate determination method:

[0082] The polycarbonate composition pellets were injection molded into impact specimens in accordance with ASTM D 256-2010.

[0083] Impact retention rate = (Ie-Ib) / Ib*100.

[0084] Among them, Ie is the impact strength after high-temperature cooking, the high-temperature cooking condition is 121°C saturated vapor pressure, the test is taken out after 96 hours, and the test is carried out after being placed at 23°C for 48 hours; Ib is the initial impact strength, which is tested after being placed at 23°C for 48 hours after injection molding.

[0085] (4) Method for measuring color difference after five passes of the machine:

[0086] The sample is added to the extruder, melt-extruded at a temperature of 270°C to 290°C, and pelletized into plastic particles to obtain 1-cycle processed particles; the 1-cycle processed particles are then added to the extruder, melt-extruded at a temperature of 270°C to 290°C, and pelletized into plastic particles to obtain 2-cycle processed particles; the 2-cycle processed particles are then added to the extruder, melt-extruded at a temperature of 270°C to 290°C, and pelletized into plastic particles to obtain 3-cycle processed particles; the 3-cycle processed particles are then added to The obtained particles were put into an extruder, melt-extruded at a temperature of 270°C to 290°C, and pelletized into plastic pellets to obtain 4-cycle processed particles. The 4-cycle processed particles were then added to an extruder, melt-extruded at a temperature of 270°C to 290°C, and pelletized into plastic pellets to obtain 5-cycle processed particles. The 1-cycle processed particles and the 5-cycle processed particles were respectively added to an injection molding machine, melted at a temperature of 270°C to 290°C, and made into 100mm*100mm*2mm strips to test the color difference ΔE2.

[0087] ΔE2=(ΔL 2 +△a 2 +△b 2 ) 1 / 2

[0088] L represents lightness, a represents the difference between red and green, and b represents the difference between blue and yellow

[0089] ΔL, Δa, and Δb correspond to the differences between the indexes (L, a, b) of the particles processed with one cycle and the particles processed with five cycles, respectively.

[0090] The performance of the PC materials provided in each embodiment and comparative example was tested according to the aforementioned performance testing method. The results are shown in Table 4.

[0091] Table 4 Performance test results of PC materials provided by Examples 1 to 20 and Comparative Examples 1 to 7

[0092]

[0093]

[0094] As can be seen from Table 4, the polycarbonate compositions provided by the embodiments of the present invention have good wet heat stability, the color difference after wet heat aging is not higher than 5, the impact retention rate after high temperature cooking is above 50%, and the color difference after 5 times of the machine is not higher than 5. Among them, the comprehensive performance of Example 1 is the best.

[0095] In Comparative Example 1, no active additive and titanium dioxide are added, and the impact retention rate is low, the wet heat color difference is large, the wet heat stability is poor, and the color difference after 5 times of processing is large; in Comparative Example 2, only active additives are added, and the impact retention rate is slightly improved compared with Comparative Example 1, but the improvement of the wet heat aging color difference is not obvious, and the color difference after 5 processing is large; in Comparative Example 3, only titanium dioxide is added, and the impact retention rate is relatively high, but the wet heat stability is poor, and the bubbles account for more than 80% of the total area; in Comparative Example 4, the content of active additive added is too high, and more active additives react with the terminal carboxyl group through the epoxy group of the epoxy polymer, and the product contains anthraquinone substances with chromophores, which appear yellow, resulting in a significant increase in the wet heat aging color difference, and a large color difference after 5 processing; in Comparative Example 5, the content of active stabilizer added is too low, and the impact retention rate is low; in Comparative Example 6, the content of titanium dioxide added is too low, and it does not contribute to the impact retention rate; in Comparative Example 7, the content of titanium dioxide added is too high, and the impact retention rate decreases.

[0096] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A PC composition resistant to moisture and heat and easy to process, characterized in that: The composition comprises the following components by weight: Polycarbonate 80-99 parts; 0.5~3 parts of titanium dioxide; Active additive 0.1~1 part; Other additives 0~3 parts; Among them, the active auxiliary agent is one of styrene-acrylonitrile-glycidyl methacrylate, bisphenol A diglycidyl ether, bis(2,6-diisopropylphenyl)carbodiimide or polycarbodiimide, or styrene-acrylonitrile-glycidyl methacrylate and polycarbodiimide; the average particle size of the titanium dioxide is 0.23~0.3μm; the weight average molecular weight of the polycarbonate is 10000~40000.

2. The heat-resistant and easy-to-process PC composition according to claim 1, characterized in that: The weight average molecular weight of the polycarbonate is 20,000-30,000.

3. The heat-resistant and easy-to-process PC composition according to claim 1, characterized in that: The other auxiliary agents are selected from one or more of stabilizers, flame retardants and fillers.

4. The heat-resistant and easy-to-process PC composition according to claim 3, characterized in that: The stabilizer is β-(4-hydroxyphenyl-3,5-di-tert-butyl) propionate; the flame retardant is potassium perfluorobutyl sulfonate; and the filler is talc.

5. The method for preparing the moisture-heat-resistant and well-processed PC composition according to any one of claims 1 to 4, characterized in that: The steps include: The polycarbonate, titanium dioxide, active additive and other additives are uniformly mixed, extruded and granulated to obtain a polycarbonate composition.

6. Use of the moisture-heat-resistant and well-processed PC composition according to any one of claims 1 to 4 in the preparation of outdoor PC products.

Citation Information

Patent Citations

  • High temperature and high humidity resistant polycarbonate composition and preparation method thereof

    CN109021534A

  • JP1975000300A

  • Treatment of porous glass base material for optical fiber

    JP1990018332A

  • Color stabilized compositions of polycarbonate-polyester compositions and method of stabilization

    WO1985002622A1

  • Impact-resistant modified polycarbonate compositions with a good combination of raw talc, hydrolysis- and melt stability

    WO2009118114A1